Mesozooplankton composition and abundance in a tropical estuary during monsoon season - Zakariya, Nur Zulikha; Md. Yusoff, Fatimah; Nishikawa, J.; Arshad, Aziz; Matias Peralta, Hazel Monica (Academic Journals, 2013)
The study was undertaken to determine zooplankton composition and abundance along Perak River estuarine system during the Northeast (NE) monsoon. Monthly samplings were conducted from November 2009 until February 2010. Four sampling stations were selected along the salinity gradient covering stations from the upstream down to 1 km off the coastal sea area. The zooplankton samples were collected by vertical tows using conical plankton net (100 μm mesh size). Throughout the monsoon season, a total of 11 higher taxa of zooplankton groups were recognized, of which copepods were the dominant group comprising 96% (including nauplii and copepodites) 95 and 99% of the total zooplankton abundance in the marine, estuarine and upstream station, respectively. Seventeen species of copepods from 10 genera were identified. Total zooplankton abundances recorded during the sampling period were 45.5±18.9x103, 34.9±25.9x103 and 45.9±30.5x103 individual m-3 in the upstream, estuarine and marine station, respectively. Multidimensional Scaling (MDS) analysis based on zooplankton abundance revealed three distinct groups separating the upstream from the estuarine and marine stations. Similarly, lower diversity index was recorded in the estuarine station (H’ = 2.04±0.28) compared to marine area (H’ = 2.20±0.26), suggesting that less copepod species were tolerant to the drastic changes of the estuarine environment. Low copepod densities were recorded in the beginning of the monsoon season, but progressively increased with a peak in the middle of the monsoon season. The results demonstrated that the Perak estuary was a turbid environment with drastic changes in salinity levels due to high inflow of freshwater during the monsoon season which affect the distribution of the zooplankton populations.